2022
DOI: 10.3390/s22093360
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Accelerometry, Global Navigation Satellite System, and Known Distance: A Correlational Design Study

Abstract: Background: Previous research has explored associations between accelerometry and Global Navigation Satellite System (GNSS) derived loads. However, to our knowledge, no study has investigated the relationship between these measures and a known distance. Thus, the current study aimed to assess and compare the ability of four accelerometry based metrics and GNSS to predict known distance completed using different movement constraints. Method: A correlational design study was used to evaluate the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This investigation revealed promising test-retest (IL CV = 3.22%–4.99%; MAG CV = 3.12%–3.49%) and inter-device (IL CV = 1.13%–2.67%; MAG CV = 1.61%–2.10%) reliability during all conditions. In accordance with the present results, our earlier observations demonstrated that MAG had lower intra- and inter-device CV when compared to IL and two other accelerometry-derived metrics when assessing external load while walking ( Bursais et al, 2022 ). Future studies should investigate which accelerometry derived metrics best quantify external load in sport.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This investigation revealed promising test-retest (IL CV = 3.22%–4.99%; MAG CV = 3.12%–3.49%) and inter-device (IL CV = 1.13%–2.67%; MAG CV = 1.61%–2.10%) reliability during all conditions. In accordance with the present results, our earlier observations demonstrated that MAG had lower intra- and inter-device CV when compared to IL and two other accelerometry-derived metrics when assessing external load while walking ( Bursais et al, 2022 ). Future studies should investigate which accelerometry derived metrics best quantify external load in sport.…”
Section: Discussionsupporting
confidence: 93%
“…Different accelerometry derived metrics have been used to quantity external loads and reported in the literature (Bursais et al, 2022). Accelerometry derived external loads have been assessed in field and laboratory environments (Johnstone et al, 2012a;Johnstone et al, 2012b;Johnstone et al, 2012c;Barrett, Midgley and Lovell, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in technology and analytical techniques have ushered in new opportunities within the applied sports environment. Nowadays, sports practitioners have the capability to monitor TL through the utilization of global navigation satellite systems and other microtechnology [ 5 , 6 ]. In the past, elite and professional teams might have been hesitant to share their methods, but recent research indicates their increasing willingness to participate in and publish applied research [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%